External merge in spec, CP: Complementizers projecting an argument. (28th December 2022) - Burukina, Irina
Abstract: The standard assumption that spec, CP is always an A′ position has been questioned for several languages where embedded C heads are involved in agreement and case assignment; however, the idea that no XP can be introduced in spec, CP by external merge has remained unchallenged. The article presents novel data from control phenomena in Mari (Uralic; nominative, SOV) and argues that, in this language, a particular type of C head is capable of thematically licensing an overt argument externally merged in spec, CP: the complementizer manən used in infinitival complement clauses projects a dative goal of communication. This behavior of manən follows from its dual nature: it is a semigrammaticalized verb 'say' that retains some lexical characteristics. I further suggest that the dative goal can be considered an overt realization of the addressee discourse variable, in line with the recent work on the presence of speaker, addressee, and logophoric center in syntax.